Review of the genus Eurygaster (Hemiptera: Heteroptera: Scutelleridae) of Russia - Neimorovets, Vladimir (Zootaxa, 2020)
Six species of the genus Eurygaster Laporte, 1833 are currently recorded from the territory of the Russian Federation including Eurygaster integriceps Puton, 1881, the most important pest of wheat in Russia. Determination of Eurygaster spp. to the species level remains challenging especially in the case of closely related E. integriceps, E. maura (Linnaeus, 1758), and E. testudinaria (Geoffroy, 1785). This often leads to errors in identification of these species and provides incorrect information for plant protection services. Additional features for more precise identification are discussed and a key to all species of the genus Eurygaster of Russia is provided. The key is backed up with short diagnoses of every species, original color photographs and summarized data on the distribution. Taxonomic status of E. testudinaria sinica Walker, 1867 is discussed and E. testudinaria sinica Walker, 1867 is synonymized with the nominative subspecies. Also, a key to all seven genera of Scutelleridae known from Russia is given.